2012
DOI: 10.1021/ic201849u
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Illumination of Intramolecular Communication in Ferrocene-Containingtris-β-Diketonato Aluminum(III) Complexes; Cytotoxicity of Al(FcCOCHCOCF3)3

Abstract: The series of ferrocene-containing tris-β-diketonato aluminum(III) complexes [Al(FcCOCHCOR)(3)] (R = CF(3), 1; CH(3), 2; C(6)H(5), 3; and Fc = ferrocenyl = Fe(η(5)-C(5)H(5))(η(5)-C(5)H(4)), 4) were synthesized and investigated structurally and electrochemically; complex 1 was subjected to cytotoxicity tests. (1)H NMR-spectroscopy distinguished between the mer and fac isomers of 2 and 3. Complex 1 existed only as the mer isomer. A single crystal X-ray crystallographic determination of the structure of a mer-iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
3
21
0
Order By: Relevance
“…0.4 eV higher binding energy than the peak of the mer isomer (solid lines), see Figure 2 and Table 1. The higher binding energy of the fac isomer is in agreement with published results [29], as well as experimental evidence of a similar Al compound, which showed that in solution only the mer isomer is present [43]. This implies that the mer isomer is more stable and in XPS the more stable isomer would be detected at the lowest binding energy.…”
Section: Resultssupporting
confidence: 91%
“…0.4 eV higher binding energy than the peak of the mer isomer (solid lines), see Figure 2 and Table 1. The higher binding energy of the fac isomer is in agreement with published results [29], as well as experimental evidence of a similar Al compound, which showed that in solution only the mer isomer is present [43]. This implies that the mer isomer is more stable and in XPS the more stable isomer would be detected at the lowest binding energy.…”
Section: Resultssupporting
confidence: 91%
“…In addition, diferrocenyl diketone 5 was applied as a starting material for the synthesis of the titanium, iron, and boron β-diketonato coordination complexes 10 – 12 (pathway ii ), Scheme 2 . Therefore, following two synthetic methodologies were used: either ligand exchange [ 41 ] or lithium-halide metathesis. In this respect, coordination complex 10 was accessible by the addition of TiCl 4 to a tetrahydrofuran solution containing [Li(κ 2 O , O ′-FcC(O)CHC(O)Fc)] [ 41 ] at −80 °C, and 11 by refluxing [Fe(acac) 3 ] (acac = acetylacetonate) with a 3-fold excess of 5 in acetonitrile ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, following two synthetic methodologies were used: either ligand exchange [ 41 ] or lithium-halide metathesis. In this respect, coordination complex 10 was accessible by the addition of TiCl 4 to a tetrahydrofuran solution containing [Li(κ 2 O , O ′-FcC(O)CHC(O)Fc)] [ 41 ] at −80 °C, and 11 by refluxing [Fe(acac) 3 ] (acac = acetylacetonate) with a 3-fold excess of 5 in acetonitrile ( Scheme 2 ). For the preparation of the purple dioxaborine complex 12 , diisopropylamine and [BF 3 ∙Et 2 O] were subsequently reacted with 5 at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous b-diketonate compounds with calamitic as well as non-calamitic structures, generated by a combination of the metal incorporated and the numbers of flexible chains, have been prepared and their mesomorphic properties investigated in detail [23][24][25][26][27][28][29][30]. However, ferrocene-containing b-diketones, widely used in conjugate chemistry [31] and medicinal chemistry, [32] etc., are rarely applied in the studies of metallomesogenic systems. Earlier, our research group utilized ferrocenyl long-chain alkyl b-diketones as ligands to coordinate with metal for obtaining heteropolynuclear mesogenic structures [33].…”
Section: Introductionmentioning
confidence: 99%